Estimating and Interpreting Peer and Role Model Effects from Randomly Assigned Social Groups at West Point - Lyle, David S (The Review of Economics and Statistics, 2007)
The random assignment of cadets to social groups at West Point provides a rare opportunity to highlight potentially misleading estimates of social group effects found in many studies. Estimates of contemporaneous group effects in human capital production are typically positive and significant; however, evidence in this study suggests that occurrences common to a group may account for much of this correlation. Models that address these biases provide little evidence of group effects in academic performance, although there is evidence of group influences in choice outcomes such as the selection of academic major and the decision to remain in the Army.